2013
DOI: 10.3389/fnsys.2013.00001
|View full text |Cite
|
Sign up to set email alerts
|

Cross-frequency interaction of the eye-movement related LFP signals in V1 of freely viewing monkeys

Abstract: Recent studies have emphasized the functional role of neuronal activity underlying oscillatory local field potential (LFP) signals during visual processing in natural conditions. While functionally relevant components in multiple frequency bands have been reported, little is known about whether and how these components interact with each other across the dominant frequency bands. We examined this phenomenon in LFP signals obtained from the primary visual cortex of monkeys performing voluntary saccadic eye move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
207
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(224 citation statements)
references
References 45 publications
16
207
1
Order By: Relevance
“…51 The AC location was marked on a 3-D rendered volume using MRIcron 52 by placing a 2-mm spherical mask on the location. 53 Preauricular points were also defined at the anterior roots of the tragi on MRI slices in addition to the nasion (a dent at the upper root of the nose bridge) and the inion (an external occipital proturberance). 54 In infants, these scalp markers are used in lieu of external markers (such as vitamin-E capsules or digitized channel recordings) so they should be detectable both on the participant’s head from the photographs and on his/her MRI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…51 The AC location was marked on a 3-D rendered volume using MRIcron 52 by placing a 2-mm spherical mask on the location. 53 Preauricular points were also defined at the anterior roots of the tragi on MRI slices in addition to the nasion (a dent at the upper root of the nose bridge) and the inion (an external occipital proturberance). 54 In infants, these scalp markers are used in lieu of external markers (such as vitamin-E capsules or digitized channel recordings) so they should be detectable both on the participant’s head from the photographs and on his/her MRI.…”
Section: Methodsmentioning
confidence: 99%
“…The head measurements and photographs of the infants wearing the fNIRS arrays and headgear (see earlier section for further details) were used to identify four fiducial landmarks on the 3-D-rendered MRI volume of the infant head (for similar work coregistering EEG electrodes see Ref. 53). Fiducials were placed as spherical masks (i) on the MRI volume at the front of the headgear over a centered marker on the headband which was aligned with the nasion, (ii) on the right and left sides at the lower-middle optode location which on an average 4- to 6-month-old infant are aligned with the preauricular points (or T3 and T4: 10 to 20 system), and (iii) over the rear at the location where the bottom of the headband met the medial location on the head.…”
Section: Methodsmentioning
confidence: 99%
“…In these studies, listeners are presented with degraded speech, or must simultaneously engage in a distracting task (cf. Mattys, Davis, Bradlow, & Scott, 2012; Mattys & Liss, 2008; Rönnberg, Lunner, Zekveld, Sörqvist, Danielsson, Lyxell, et al, 2013). …”
Section: Suboptimal Conditionsmentioning
confidence: 99%
“…They found that emotional processing depends on the overt attentional resources. Ito et al (2013) observed interaction between low and high frequency components in the local field potentials (LFP) recorded in the visual cortex of monkeys performing voluntary saccades during natural scene viewing. They concluded that the cross-frequency interaction is a manifestation of the mechanism which coordinates oculomotor behavior and sensory processing.…”
mentioning
confidence: 99%
“…The most common methodological approach is examination of the EEG activity time-aligned to certain eye movement events, such as the onset of a fixation or a start of a saccadic eye movement (Fischer et al, 2013;Frey et al, 2013;Henderson et al, 2013;Hutzler et al, 2013;Nikolaev et al, 2013;Richards, 2013;Simola et al, 2013). Several works employ the time-frequency and synchrony analysis (Fischer et al, 2013;Hoffman et al, 2013;Ito et al, 2013;.…”
mentioning
confidence: 99%